If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + -1(7q + 13) = 8 + -1(11q + -4) Reorder the terms: 4q + -1(13 + 7q) = 8 + -1(11q + -4) 4q + (13 * -1 + 7q * -1) = 8 + -1(11q + -4) 4q + (-13 + -7q) = 8 + -1(11q + -4) Reorder the terms: -13 + 4q + -7q = 8 + -1(11q + -4) Combine like terms: 4q + -7q = -3q -13 + -3q = 8 + -1(11q + -4) Reorder the terms: -13 + -3q = 8 + -1(-4 + 11q) -13 + -3q = 8 + (-4 * -1 + 11q * -1) -13 + -3q = 8 + (4 + -11q) Combine like terms: 8 + 4 = 12 -13 + -3q = 12 + -11q Solving -13 + -3q = 12 + -11q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '11q' to each side of the equation. -13 + -3q + 11q = 12 + -11q + 11q Combine like terms: -3q + 11q = 8q -13 + 8q = 12 + -11q + 11q Combine like terms: -11q + 11q = 0 -13 + 8q = 12 + 0 -13 + 8q = 12 Add '13' to each side of the equation. -13 + 13 + 8q = 12 + 13 Combine like terms: -13 + 13 = 0 0 + 8q = 12 + 13 8q = 12 + 13 Combine like terms: 12 + 13 = 25 8q = 25 Divide each side by '8'. q = 3.125 Simplifying q = 3.125
| x+20+x+10+x=180 | | 27-6m=m^2 | | 7x-36-6x+12= | | x+2y-1=180 | | 19x-(7x-9)=45 | | 50y-42=45y+60 | | 7.5=1.5x+45 | | 24x-5-16x+2=18x-9-10x+15 | | (x-4)(x+4)(2x+11)=0 | | 2y+4(y-6)=8y-4(y-10) | | x=(5x+15)(6x-10) | | y=5x^2+13x+3 | | (x^2+6)+(2xi)=0 | | 3x+13-6x=18-15x+12x-5 | | 5r+-3r+2=5r-r | | (x-3)(x+1)(x-4-2i)(x-4+2i)=0 | | 7(x-9)+4=7x+7 | | x=(6x-10)(6x+10) | | 3x-45=56 | | 8+5x=7x+8 | | -3(-4p+5)=5(6p+15) | | -14.3=5.7-4y | | 4a-b=.5 | | 3x+13-6x=15x+12x-5 | | x-(4.50+1.99+0.39)=13.12 | | 3x+2y-2=180 | | 3y=2x-15 | | y=x^2-8x+195 | | (2x^2+6x-3)+(2x^3-3x+2)= | | 3x+2=-3x+20 | | 2x+8=3x*x+4 | | -9-x=6x-79 |